Minor head injury in the Republic of Ireland: evaluation of written information given at discharge from emergency departments. Issue 8 (10th November 2010) - Peachey, Tom; Hawley, Carol A; Cooke, Matthew; Mason, Lynda; Morris, Richard
Abstract : Most patients presenting to the emergency department with minor head injuries are discharged with written information. Here the quality of minor head injury discharge leaflets in the Republic of Ireland is evaluated against a nationally accepted template. There was great variability in leaflet content. Most provided minimal information on emergency symptoms but 60% contained no information on post-concussional symptoms. No leaflet was available in audio-format or languages other than English. Information provided in minor head injury leaflets should be improved and standardised across Ireland.